2021
DOI: 10.32942/osf.io/r3pd2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hybridization may promote variation in cognitive phenotypes in experimental guppy hybrids

Abstract: Hybridization is an underappreciated mechanism of evolution. While hybrids often express inferior traits and are selected against, hybridization can promote phenotypic variation and produce trait combinations distinct from the parentals, generating novel adaptive potential. Among other traits, hybridization can impact behaviour and cognition and may reinforce species boundaries when hybrids show decreased cognitive abilities. However, the hypothesized role of hybridization in the diversification of cognitive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…To address this empirical gap, here we investigated the effect of hybridization on brain anatomy, learning ability, and cognitive flexibility in F1 and F2 hybrids of two closely related fish species (Poecilia reticulata and P. wingei). Our previous study of learning ability and cognitive flexibility in F1 females of this cross showed that female hybrids had slightly higher phenotypic dispersion, some hybrid individuals had transgressive trait scores, and the mean phenotype of one hybrid group deviated away from the axis of variation of the parentals, suggesting that hybridization may promote cognitive variation and generate new trait combinations (Vila Pouca et al 2022). These results on F1 female hybrids provided an important first test of whether hybridization can promote cognitive variation, a prerequisite for hybrids to have cognitive innovation potential (Seehausen 2013;Selz and Seehausen 2019).…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…To address this empirical gap, here we investigated the effect of hybridization on brain anatomy, learning ability, and cognitive flexibility in F1 and F2 hybrids of two closely related fish species (Poecilia reticulata and P. wingei). Our previous study of learning ability and cognitive flexibility in F1 females of this cross showed that female hybrids had slightly higher phenotypic dispersion, some hybrid individuals had transgressive trait scores, and the mean phenotype of one hybrid group deviated away from the axis of variation of the parentals, suggesting that hybridization may promote cognitive variation and generate new trait combinations (Vila Pouca et al 2022). These results on F1 female hybrids provided an important first test of whether hybridization can promote cognitive variation, a prerequisite for hybrids to have cognitive innovation potential (Seehausen 2013;Selz and Seehausen 2019).…”
Section: Introductionmentioning
confidence: 77%
“…Common guppy (Poecilia reticulata) populations descended from wild individuals from the upper Aripo river, Trinidad, and Endler's guppy (P. wingei) populations descended from wild individuals from Cumaná, Venezuela in 2006. Experimental fish were produced according to standard hybridization methods (Stelkens et al 2009;Vila Pouca et al 2022). In brief, non-hybrid (parental) crosses and reciprocal first-generation (F1) hybrids (i.e., P. reticulata females crossed with P. wingei males, and P. wingei females crossed with P. reticulata males) were bred simultaneously, in January and August 2020.…”
Section: Parental Species and Hybrid Breedingmentioning
confidence: 99%
See 3 more Smart Citations